2007
DOI: 10.1371/journal.pone.0001061
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Genes Are the Evolutionarily Conserved Targets of the E2F4 Transcription Factor

Abstract: Maintaining quiescent cells in G0 phase is achieved in part through the multiprotein subunit complex known as DREAM, and in human cell lines the transcription factor E2F4 directs this complex to its cell cycle targets. We found that E2F4 binds a highly overlapping set of human genes among three diverse primary tissues and an asynchronous cell line, which suggests that tissue-specific binding partners and chromatin structure have minimal influence on E2F4 targeting. To investigate the conservation of these tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 40 publications
7
43
1
Order By: Relevance
“…The occupancy of E1A at the MCM4 promoter was quite different from what we observed with the PCNA promoter. Unlike at the PCNA promoter, E2F4 was not previously reported to be present at the MCM4 promoter (7,9,27). During infection with virus expressing E1A 13S alone (pm975), E1A was present at the MCM4 promoter at a relatively high level (ϳ8% of the input; Fig.…”
Section: Vol 85 2011mentioning
confidence: 80%
“…The occupancy of E1A at the MCM4 promoter was quite different from what we observed with the PCNA promoter. Unlike at the PCNA promoter, E2F4 was not previously reported to be present at the MCM4 promoter (7,9,27). During infection with virus expressing E1A 13S alone (pm975), E1A was present at the MCM4 promoter at a relatively high level (ϳ8% of the input; Fig.…”
Section: Vol 85 2011mentioning
confidence: 80%
“…This means that considerable differences in the biochemical pathways regulated by the transcription factors analysed are to be expected. Indeed, when analysing the Gene Ontology [55] categories that are enriched in different gene sets, species-specific gene targets correspond to novel functions regulated by the transcription factor under study [14,15,20,23]. Tuch et al [15] found that the transcription factor Mcm1 bound a conserved set of only 12 genes in S. cerevisiae, Kluyveromyces lactis and C. albicans, and there was enrichment for functional terms related to cell cycle and mating type.…”
Section: (C) Binding Event Turnover and Differences In Biochemical Pamentioning
confidence: 99%
“…Understanding the full regulatory potential of the cell cycle machinery in the brain therefore necessitates an appreciation of the repertoire of E2f target genes in NPCs. Genome-wide targets have been reported for E2f4 (and E2f1) in a number of immortalized and transformed cell lines, 20,22,23 and for E2f3 in immortal mouse myoblasts, myotubes and embryonic fibroblasts. 24,25 E2f targets have, however, not been identified on a genome-wide level in any neural cells, nor in any primary cell types.…”
mentioning
confidence: 99%